2021
DOI: 10.3390/ijerph18052346
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Stress-Scale Specifically Designed to Measure Stress of Women with Newly Diagnosed Breast Cancer

Abstract: Most breast cancer patients are middle-aged women actively involved in establishing a family, developing a career, or raising children. With the exception of the Newly Diagnosed Breast Cancer Stress Scale (NDBCSS), few stress scales have been designed for women with breast cancer. This study checked the dimensionality of the NDBCSS by confirmatory factor analysis (CFA) and the results showed a poor fit, indicating an urgent need for improvement. Exploratory factor analysis (EFA) using the varimax rotation meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Thus, the cognitive displacement of individuals might affect their physical behaviour, which can alter how victims relate with colleagues and other people at the workplace. This result corroborates other previous studies which have documented an unfavourable effect of excessive alcohol consumption on consumers' mood (Alford et al, 2020), workplace productivity (Łyszczarz, 2019;Stepanek et al, 2019) and presenteeism (Buvik et al, 2018;Lee et al, 2021). Past studies on stress have also documented its negative effect on job performance (Aduma et al, 2022;Akah, Owan, Aduma, et al, 2022;Daniel, 2019) and other work-related variables such as productivity (Ma & Ye, 2019;Ramos-Galarza & Acosta-Rodas, 2019) and job satisfaction (An et al, 2020;O'Brien et al, 2019).…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the cognitive displacement of individuals might affect their physical behaviour, which can alter how victims relate with colleagues and other people at the workplace. This result corroborates other previous studies which have documented an unfavourable effect of excessive alcohol consumption on consumers' mood (Alford et al, 2020), workplace productivity (Łyszczarz, 2019;Stepanek et al, 2019) and presenteeism (Buvik et al, 2018;Lee et al, 2021). Past studies on stress have also documented its negative effect on job performance (Aduma et al, 2022;Akah, Owan, Aduma, et al, 2022;Daniel, 2019) and other work-related variables such as productivity (Ma & Ye, 2019;Ramos-Galarza & Acosta-Rodas, 2019) and job satisfaction (An et al, 2020;O'Brien et al, 2019).…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…This finding supports the study's result that stress significantly impacts graduate students' capacity to learn and perform in the workplace (Pascoe et al, 2020). A previous study also found that very high levels of persistent mental stress were linked to worse academic performance (Lee et al, 2021). The positive mediation of PE on the nexus between AC and TW may be attributed to mood.…”
Section: Discussion Of Findingssupporting
confidence: 86%
See 2 more Smart Citations
“…The individual perception of stress depends on personality, learning, and culture (Folkman, 2011). Some measures of perceived stress have been developed specifically for the cancer context, for example, the Questionnaire on Stress in Cancer Patients (Herschbach et al, 2003), which assesses cancer-specific stress situations, and the Newly Diagnosed Breast Cancer Stress Scale (Lee et al, 2013(Lee et al, , 2021, which measures perceptions of stress at the beginning of the breast cancer process.…”
mentioning
confidence: 99%